Sphecidae sensu lato (Hymenoptera: Apoidea) of the Jazan Province, south-west of Saudi Arabia, with the description of two new species - Gadallah, Neveen S.; El-Ghiet, Usama M. Abu (Zootaxa, 2024)
Exactly 100 species of Sphecidae sensu lato (Hymenoptera) in 37 genera have been recorded from the Jazan Province, south-west of Saudi Arabia. They represent 33% of the total sphecid wasps of Saudi Arabia. They are all listed, and distribution in different areas of Jazan and their collecting periods are provided for each species. In the present study, the female of Dolichurus arabicus is discovered in Saudi Arabia from Jazan. Two new species, Dolichurus pseudobimaculatus Gadallah, and Entomognathus sauditus Gadallah, respectively from Abu Arish and Fayfa, are described and illustrated and Dolichurus arabicus Ohl, Harpactus formosus (Jurine), and Encopognathus bellus (Dalla Torre) are recorded for the first time from Jazan (Abu Arish).